Embedding Ethical Principles into Generative AI Workflows for Project Teams - Venkatraman Viswanathan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The integration of ethical principles into generative AI workflows is critical as project teams increasingly rely on AI tools for collaborative tasks such as content creation, ideation, and decision support. This paper investigates the ethical dimensions of generative AI use within team-based environments, emphasizing principles of transparency, fairness, accountability, and privacy. Drawing on current ethical frameworks and industry guidelines, the study identifies implementation challenges at the workflow level, including bias propagation, lack of explainability, and uneven responsibility assignment. A practical framework is proposed to embed ethics into AI workflows across key project stages. Supported by case studies and qualitative analysis, the findings highlight how ethical design fosters trust, improves team dynamics, and enhances the reliability of AI-assisted outcomes.